EFFECTS OF ANOLYTE WATER ON THE CLASSICAL SWINE FEVER VIRUS: EFFECTS OF OXIDANTS AND pH - KARADZHOV, STOIL; IVANOVA, EMILIYA; IGNATOV, IGNAT; ATANASOV, ATANAS (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
The aim of the analyses was to examine the interaction between anolyte and its compounds and classical swine fever virus. The results on the anti viral action of acidic electrochemically activated water solution anolyte are prersented. It was produced in the anode chamber of the electrolitic cell (electrolyzer). The main stage of the electrochemical treatment of water occurs in the electrolysis’ cell, consisting of cathode and anode separated by a special semipermeable membrane (diaphragm). The diaphragm separates water to alkaline fraction (catholyte) and acidic one (anolyte). The classical swine fever (CSF) virus was treated with anolyte under laboratory conditions in the cell culture and suspensions. The assay of determination of Colony Forming Units (CFU) was used. The results were achieved with immunoperoxidase technique after inoculating them with cell cultures. There presence of viral antigens was measured. It was found that anolyte did not affect the growth of the cell culture PK-15. The viral growth during the infection of a cell monolayer with a cell culture virus was affected in the greatest degree by the anolyte in 1:1 dilution. The results were less in other dilutions.